Medical Writing: Challenges in the Contemporary Era - Iqbal Hussain Udaipurwala (Journal of Bahria University Medical and Dental College)
Publication of a research article in medical journal is reflection of scholarly activity and academic credentials.1 History of medical writing dates back to very ancient times but in the contemporary era, medical writing has been changed a lot and also changing continuously with each passing day. The time was not far in the past when the dictum “publish or perish” was popular but soon only “publish” was not enough. This noble statement is constantly changing its form to become “publish in a good journal or perish”, then “publish in impact factor journal or perish”, “publish in high impact factor or perish”, “continuously publish in high impact factor journal or perish” and so on. Medical writing also became important in our region when academic promotions were made dependent on number of scientific publications